Yolk colour of eggs from different housing systems - Bertoncelj, Jasna (Array, 2019)
Eggs are nutrient-dense food with high biological value. They are a good source of protein, essential fatty acids and amino acids, vitamins and minerals. The colour of egg yolks is one of the important factors used to evaluate eggs’ quality and is affected by the composition of poultry feed, mostly the pigment content, laying hens housing system and also genetic effects. In this study the colour of egg yolks from eggs produced in different housing systems was evaluated. DSM colour fan, Minolta chromameter and the AOAC method for determination of total carotenoid content were used. The results showed that there are differences in egg yolks colour according to the type of housing system. The most noticeable differences were detected between organic and caged eggs. Organic egg yolks were the brightest and contained the least carotenoids, while cage egg yolks were the darkest, with the highest content of carotenoids. The colour of egg yolks was also evaluated with sensory analysis. The sensory panel consisted of young consumers – students, who ranked the samples according to the intensity and likeness of the yolk colour. The students gave preference to orange-yellow colour of egg yolk. Results of the short questionnaire about consumption and purchase of eggs showed that participating students do not consume eggs often. The most important criterion for the purchase is egg production system, where free-range or barn eggs with more intense colour are preferred.